Gamma and Decay Energy Spectroscopy Measurements of Trinitite. (11th October 2021) - Mercer, David J.; Koehler, Katrina E.; Croce, Mark P.; Hoover, Andrew S.; Hypes, Philip A.; Kozimor, Stosh A.; Mocko, Veronika; Saey, Paul R. J.; Schmidt, Daniel R.; Ullom, Joel N.
Abstract: We report gamma-ray spectroscopy measurements of trinitite samples and analogous samples obtained from detonation sites in Nevada and Semipalatinsk, as well as in situ measurements of topsoil at the Trinity site. We also report the first isotopic composition measurements of trinitite using the novel forensics technique of decay energy spectroscopy (DES) as a complement to traditional forensics techniques. Our gamma spectroscopy and DES measurements are compared to other published results.